The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/medicines5020049
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Four Solanum spp. Extracts in an Animal Model of Cutaneous Leishmaniasis

Abstract: Background: Leishmaniasis is a complex protozoa disease caused by Leishmania genus (Trypanosomatidae family). Currently, there have been renewed interests worldwide in plants as pharmaceutical agents. In this study, the in vivo efficacy of Solanum spp. is assessed in an L. amazonensis BALB/c mice model for experimental cutaneous leishmaniasis. Methods: Animals were infected with 5 × 106 metacyclic promastigotes and 30-day post-infection, a treatment with 30 mg/kg of Solanum extracts or Glucantime® (GTM) was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
3
0
1
Order By: Relevance
“…While several reports have demonstrated the leishmanial efficacy of Glucantime ® in vivo, herein we did not observe reductions in parasite load in our in vivo murine model of L. amazonensis. However, our data does corroborate previous reports detailing the ineffectiveness of Glucantime ® in reducing parasite load in L. amazonensis-infected BALB/c mice inoculated in the ear or footpad (Cos et al, 2018;Cavalcanti de Queiroz et al, 2019;Valentim Silva et al, 2020). Furthermore, it is important to highlight the divergent results in the scientific literature regarding important issues, such as dosage, quantity of inoculated Leishmania (10 5 -10 7 ), and the model of cutaneous leishmaniasis employed (ear pinna, hind footpad or tail base), all of which may influence disease severity and outcome, as well as pharmacologic response (Loeuillet et al, 2016;Paladi et al, 2017;Coelho et al, 2016;Kauffmann et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…While several reports have demonstrated the leishmanial efficacy of Glucantime ® in vivo, herein we did not observe reductions in parasite load in our in vivo murine model of L. amazonensis. However, our data does corroborate previous reports detailing the ineffectiveness of Glucantime ® in reducing parasite load in L. amazonensis-infected BALB/c mice inoculated in the ear or footpad (Cos et al, 2018;Cavalcanti de Queiroz et al, 2019;Valentim Silva et al, 2020). Furthermore, it is important to highlight the divergent results in the scientific literature regarding important issues, such as dosage, quantity of inoculated Leishmania (10 5 -10 7 ), and the model of cutaneous leishmaniasis employed (ear pinna, hind footpad or tail base), all of which may influence disease severity and outcome, as well as pharmacologic response (Loeuillet et al, 2016;Paladi et al, 2017;Coelho et al, 2016;Kauffmann et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Some positive results were obtained with IL-Sb V in a hamster CL model (100 % lesion reduction and no parasites in organs) (Travi, et al, 1993;Yépez, et al,1999); however, no complete cure of CL-infected mice has been documented. Per example, treatment of mice infected with L. (L.) amazonensis, with IL-Sb V 28 mg/kg/day × 5, every 4-5 days resulted in partial parasite burden reduction with no increase in footpad thickness, but not in cure (Cos et al, 2018;Fournet et al, 1996). Differences in numbers of Sb V -IL sessions, dose, site of infection, parasite species, and followup time could explain the different results obtained in this study.…”
Section: Discussionmentioning
confidence: 65%
“…On a comparative evaluation with synthetic antibiotics, the antibacterial activity of methanol extracts of A. lebbeck and S. seaforthianum was comparable with the synthetic antimicrobial agent's erythromycin and fluconazole. The review of literature revealed that the extracts of A. lebbeck and S. seaforthianum showed antimicrobial, antioxidant, antidiabetic, antimalarial, antiarthritic, and anti-allergic properties [17][18][19][20][21][22][23][24][25][26][27]. Ali et al [17] from Bangladesh evaluated the antimicrobial and antioxidant activity of petroleum ether, ethyl acetate and methanol extracts of A. lebbeck against B. subtilis, S. aureus, V. mimicus, S. typhi, S. dysenteriae, C. arrizae, and A. niger.…”
Section: Discussionmentioning
confidence: 99%